Spatial distribution of biomass consumption as energy in rural areas of the Indo-Gangetic plain - Saud, T.; Singh, D.; Mandal, T.; Gadi, R.; Pathak, H.; Saxena, M.; Sharma, S.; Gautam, R.; Mukherjee, Abhijit; Bhatnagar, R. (Pergamon, 2011)
Biomass is widely used as energy source in rural households in India. Biomass samples and socio-economic data have been collected at district level in the rural areas of Indo-Gangetic plain (IGP), India to determine the emissions of trace gases and aerosols from domestic fuels. Dung cake, fuelwood and crop residue are main sources of energy in rural areas of the IGP. Dung cake is the major domestic fuel (80-90%) in the rural areas of Delhi, Punjab, Haryana, Uttar Pradesh, Bihar and West Bengal, whereas, 99% of rural households in Uttarakhand use wood as the main energy source. Using crop production data and usage of crop residues as energy, new consumption values have been estimated (21.13 Mt). Present information on the domestic fuel usage would be helpful in determining budgets estimates of trace gases and aerosols for India. © 2010 Elsevier Ltd.